2007
DOI: 10.1038/sj.clpt.6100316
|View full text |Cite
|
Sign up to set email alerts
|

CYP2C9 Genotype-guided Warfarin Prescribing Enhances the Efficacy and Safety of Anticoagulation: A Prospective Randomized Controlled Study

Abstract: Warfarin anticoagulation effect is characterized by marked variability, some of which has been attributed to CYP2C9 polymorphisms. This study prospectively examines whether a priori knowledge of CYP2C9 genotype may improve warfarin therapy. Patients were randomly assigned to receive warfarin by a validated algorithm ("control", 96 patients) or CYP2C9 genotype-adjusted algorithms ("study", 95 patients). The first therapeutic international normalized ratio and stable anticoagulation were reached 2.73 and 18.1 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
289
2
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(299 citation statements)
references
References 50 publications
6
289
2
2
Order By: Relevance
“…Combined, polymorphisms in these 2 alleles plus age, sex, and weight account for 56% to 64% of warfarin dose variation. 56,[73][74][75] Table 7 summarizes the effects of CYP2C9 and VKO-RC1 variants on warfarin dose, the effects these variants have on sensitivity to warfarin, and variant prevalence as observed and reported in 3 previously published peerreviewed reports plus results from the current report (835 patients total). The findings from these 4 unrelated studies describing the association between warfarin daily dose and genotype show considerable agreement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combined, polymorphisms in these 2 alleles plus age, sex, and weight account for 56% to 64% of warfarin dose variation. 56,[73][74][75] Table 7 summarizes the effects of CYP2C9 and VKO-RC1 variants on warfarin dose, the effects these variants have on sensitivity to warfarin, and variant prevalence as observed and reported in 3 previously published peerreviewed reports plus results from the current report (835 patients total). The findings from these 4 unrelated studies describing the association between warfarin daily dose and genotype show considerable agreement.…”
Section: Discussionmentioning
confidence: 99%
“…This pharmacogenetic equation explained 53% to 54% of the variability in the warfarin dose in a validation cohort of 292 patients. Caraco et al 73 studied 96 patients treated prospectively with warfarin and knowledge of warfarin sensitivity genotype. Patients treated in the genotyping arm of this study reached target INR 2.8 days earlier and stable warfarin dose 19 days earlier compared with 96 control patients matched for age, sex, body weight, body mass index, smoking status, indications for treatment, clinical characteristics, and co-medications treated without knowledge of genotype.…”
Section: Effect Of Allelic Variants On Warfarin Activitymentioning
confidence: 99%
“…Results from two small trials have recently been reported [95,96]. One trial of 191 patients, using CYP2C9-based dosing (not including VKORC1 or clinical variables), demonstrated a significant improvement in both primary outcomes: the time to reach the first therapeutic INR (2.73 days earlier with CYP2C9-based dosing versus empiric dosing) and the time to reach maintenance dose (18 days earlier with CYP2C9-based dosing versus empiric dosing) [96].…”
Section: Expert Opinionmentioning
confidence: 99%
“…However, in the prevention of thrombotic events with atrial fibrillation, the polymorphic cytochrome P450 2C9 (CYP2C9) protein is accepted as the rate-limiting drug-metabolizing enzyme of warfarin clearance and, to less extent, also to the clearance of alternative vitamin K antagonists, such as acenocoumarol and phenprocoumon. A prospective study addressing the question of whether a priori knowledge of CYP2C9 genotype may improve warfarin therapy demonstrated that patients who were treated applying a CYP2C9 genotype-adjusted algorithm reached a significantly earlier stable anticoagulation state and experienced less minor bleeding [3] than those who were not. Moreover, subjects who are carriers of variants in the vitamin K epoxide reductase complex, subunit 1 (VKORC1) gene require significantly higher warfarin doses than usually recommended [5,30].…”
Section: Application Of Personal Medicine In Clinical Practicementioning
confidence: 99%